2022
DOI: 10.2147/idr.s355742
|View full text |Cite
|
Sign up to set email alerts
|

Clinico–Epidemio-Microbiological Exploratory Review Among COVID-19 Patients with Secondary Infection in Central India

Abstract: Purpose Secondary infections (SI) in COVID-19 have been documented from 3.6% to 72% in various studies with mortality ranging from 8.1% to 57.6%. There is a gap in knowledge for clinico–epidemio-microbilogical association among COVID-19 patients with concomitant SI. Patients and Methods This is a retrospective chart review, in central India. The study was undertaken for hospitalized adult patients during 1st June 2020 to 30th November 2020, with laboratory proven COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A systematic review and meta-analysis showed a high prevalence of antimicrobial resistance (AMR) in COVID-19 patients, with the most common microorganisms represented by MRSA, carbapenem-resistant A. baumannii, Klebsiella pneumonia e and Pseudomonas aeruginosa , and multi-drug resistant Candida auris ( 11 ). High rates of carbapenem resistance in Acinetobacter spp., K. pneumoniae and other Enterobacterales have also been reported in single studies where the above microorganisms represented the predominant causes of BSI in patients hospitalized with COVID-19 ( 12 , 13 ). Both prevalence of BSI and rates of resistance, however, displayed wide heterogeneity by hospital and geographical area ( 8 13 ).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…A systematic review and meta-analysis showed a high prevalence of antimicrobial resistance (AMR) in COVID-19 patients, with the most common microorganisms represented by MRSA, carbapenem-resistant A. baumannii, Klebsiella pneumonia e and Pseudomonas aeruginosa , and multi-drug resistant Candida auris ( 11 ). High rates of carbapenem resistance in Acinetobacter spp., K. pneumoniae and other Enterobacterales have also been reported in single studies where the above microorganisms represented the predominant causes of BSI in patients hospitalized with COVID-19 ( 12 , 13 ). Both prevalence of BSI and rates of resistance, however, displayed wide heterogeneity by hospital and geographical area ( 8 13 ).…”
Section: Introductionmentioning
confidence: 82%
“…With respect to fungal isolates, our results are consistent with those of Karuna et al, that describe a low rate of azole resistance in Candida spp. isolated from BSI ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation